探究式教學融入教育心理學課程之行動研究 Action Research of Integrating Inquiry-based Instruction in an Educational Psychology Course - 王佳琪 Chia-Chi Wang (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2022)
本研究以行動研究的方式，探討探究式教學融入教育心理學課程的實施情形，以及對師資培育者專業成長的影響。研究對象為某師資培育中心修教育心理學課程的師資生 20名，共歷時一學期。研究過程中，研究者以「學生探究能力學習單」、「課堂學習氣氛問卷」、「課堂觀察紀錄表」、「教學研究日誌」、「學生作業」與「教學意見回饋」等方式蒐集資料。結果發現，藉由核心問題與層次性提問能有效營造教室探究文化，提高師資生的學習投入，進而展開自主探究學習；在探究步驟中，善用多元評量與具體回饋，讓師資生的學習變得可見；師生亦從探究中形成專業知識與理念，產生理論與實務的連結與意義。再者，研究者亦從反思中強化了探究教學信念，弭平教學壓力與成果的衝突，進而建構出探究教學轉化模式，其結果能提供師資培育課程之探究教學建議。 This research explored the implementation of an inquiry-based instruction integrated into the curriculum and its impact on the professional growth of the teacher educator using action research. Participants in this study were 20 pre-service teachers who attended an Educational Psychology course. The researcher collected multiple data from the participants’ responses for Student Inquiry Ability Checklist, the class learning atmosphere questionnaire, the teaching and reflection journals, and the pre-service teachers’ reports in class. The findings indicated that essential questions and questioning regarding Educational Psychology could be used to effectively create a classroom with a culture of inquiry, increase preservice teachers’ engagement in class, and carry out self-directed inquiry learning. During the process, the researcher made good use of multiple assessments and specific feedback to raise pre-service teachers’ performance. It can be seen that the researcher and pre-service teachers constructed professional knowledge and ideas and generated connections and meanings between theory and practice. During this process, the researcher strengthened their belief in inquiry-based instruction from reflection, reduced the conflict between teaching pressure and student learning outcome and constructed a transforming model of inquiry-based instruction. Suggestions for implementing a similar curriculum were proposed for future studies.